Effectıveness on Usage of E-Hrm ın Publıc Sector Organısatıons - Dr.S.Gomathı, Uagayathrı.Kuragantı (International Journal of Advanced Science and Technology, 2020)
This paper is to know about the Usage of Technology and Information System by the Employees in the Organisation. Through this study, we are focusing on the Usage of e-resources by Public Sector Organisations. There are various Functions in HR, such as Employee Attendance, Payroll, Compensation, Training, Performance Appraisal, Feedback, Social Networking, and Usage of Information System. Social Networking also helps in enhancing the working relationship of employees, which analyzed in our study. Every function uses e-resources in different ways in the Organisation. From this study, we can identify whether employees are creating the work efficiently using e-resources in Human resource management functions in the Organization